EFEKTIFITAS SOUTH ASIA FREE TRADE AGREEMENT (SAFTA) DALAM MENINGKATKAN LIBERALISASI PERDAGANGAN INTRA-KAWASAN SOUTH ASIAN ARRANGEMENT OF REGIONAL COOPERATION (SAARC) TAHUN 2007-2010 - Dilika Putri; Pazli " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research of this thesis is aimed to recognize the obstacles which are cause the failure of SAFTA in SAARC economy integrating process. The purpose of this thesis more specificly can be seen such as: 1. Describing the failure of SAFTA in improving the intra-regional trading liberalitation of SAARC in 2007-2010. 2. Describing the obstacles of improving the intra-regional trading liberalitation of SAARC. Data collection techniques that do a library research of the literature relevant to the subject matter in the object of research, whether it be books, journals, articles sourced from the internet or newspapers. Data analysis technique used the qualitative analysis. Relevant data collected and analyzed qualitatively, by linking these phenomena with one to another, to get final conclusions.In spite of South Asia free trade cooperation by South Asian Preferential Trade Agremeent (SAPTA) in 1995 and South Asian Free Trade Agreement (SAFTA) in 2006, there is still low percentage of intra-regional trade, especially export volume, compared with their total world export. However, its ratio percentage was 4-6% , whereas Eropa Union was 57-65%, ASEAN was 22-25%, and NAFTA was 48-55% within 2000-2010.The main cause is the incomplementary of their products export both in economy and political perspective. It means that they yield the similiar products, in particularly textile products, so that they have to relocate and sell their export products to outside regional countries, such as United States and Eropa Union, instead of making trade with SAARC members.Keywords : SAARC, SAPTA, SAFTA, incomplementary of their products , industrial policy, and trade policy